Microsoft Office Word 2007 inside out - Murray, Katherine 1961- (Microsoft Press, 2007)
You're beyond the basics with Word, so dive right in and really put your content to work! This supremely organized reference is packed with hundreds of timesaving solutions, troubleshooting tips, and workarounds. It's all muscle and no fluff. Discover how the experts tackle Word 2007-and challenge yourself to new levels of mastery.